2018
DOI: 10.3390/molecules23092306
|View full text |Cite
|
Sign up to set email alerts
|

Tetrahydroxystilbene Glucoside Regulates Proliferation, Differentiation, and OPG/RANKL/M-CSF Expression in MC3T3-E1 Cells via the PI3K/Akt Pathway

Abstract: Tetrahydroxystilbene glucoside (TSG) is a unique component of the bone-reinforcing herb Radix Polygoni Multiflori Preparata (RPMP). It has the ability to promote bone formation and protect osteoblasts. However, the underlying mechanism remains unclear. To better understand its biological function, we determined TSG’s effect on murine pre-osteoblastic MC3T3-E1 cells by the MTT assay, flow cytometry, FQ-PCR, Western blot, and ELISA. The results showed that TSG caused an elevation of the MC3T3-E1 cell number, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…Our outcomes showed that PI3K-AKT signaling pathway was activated on SLM-AHT surface, combing with high expression of integrin α2. Since PI3K-AKT signaling had been proved involved in multiple cell functions including cell proliferation, apoptosis, growth, glucose metabolism, migration and differentiation (Gu et al, 2013;Choi et al, 2014;Xu et al, 2015;Fan et al, 2018), we supposed that there might be crosstalk between integrin α2 and PI3K-AKT signaling pathway, and hierarchical micro-nano topography by itself could affect this integrin α2-PI3K-AKT signaling axis. However, whether integrin α2 could activate PI3K-AKT signaling pathway was still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Our outcomes showed that PI3K-AKT signaling pathway was activated on SLM-AHT surface, combing with high expression of integrin α2. Since PI3K-AKT signaling had been proved involved in multiple cell functions including cell proliferation, apoptosis, growth, glucose metabolism, migration and differentiation (Gu et al, 2013;Choi et al, 2014;Xu et al, 2015;Fan et al, 2018), we supposed that there might be crosstalk between integrin α2 and PI3K-AKT signaling pathway, and hierarchical micro-nano topography by itself could affect this integrin α2-PI3K-AKT signaling axis. However, whether integrin α2 could activate PI3K-AKT signaling pathway was still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, traditional Chinese medicines (TCMs) have been attracting increasing attention from researchers because of their pharmacological activities, including antiosteoporotic effects, and exhibition of fewer adverse effects. OP is thought to be mainly caused by kidney deficiency [11]; thus, kidney-tonifying TCM is expected to effectively treat OP. Yishen Bugu Ye (YSBGY) is a TCM composed of 12 types of medicinal herbs, namely, Rhizoma Drynariae, Radix Polygoni Multiflori, Poria, Radix Dipsaci, Radix Paeoniae Alba, Radix Angelica sinensis, Radix Codonopsis, Radix Rehmanniae Preparata, Rhizoma Polygonati, Fructus Lycii, Pyritum, and Pericarpium Citri Reticulatae, and has long been used in China for protecting the kidneys and improving tendon and bone strength.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown to increase callus formation and osseointegration, enhance bone strength at the femoral diaphysis in osteoporotic fractures, and restore the femur trabecular bone mineral density (BMD) in female Sprague-Dawley osteoporotic fracture model rats [13]. In addition, Radix Polygoni Multiflori has been shown to promote the proliferation and differentiation of MC3T3-E1 cells by increasing the mRNA concentrations of runt-related transcription factor-2 (Runx2), osterix (Osx), and osteopontin (OPN) and reducing those of RANKL [11]. Radix Rehmanniae Preparata has been reported to improve the microstructure of trabecular bone in rats with dexamethasone-(Dex-) induced OP [14].…”
Section: Introductionmentioning
confidence: 99%
“…PI3K/AKT signaling is a cell-growth-regulatory pathway involved in many diseases 52, 53. Previous studies54, 55 suggested that this pathway is essential for the differentiation of bone progenitor cells. Fan et al 54 .…”
Section: Discussionmentioning
confidence: 99%